Mitochondrially targeted ZFNs for selective degradation of pathogenic mitochondrial genomes bearing large‐scale deletions or point mutations. Issue 4 (24th February 2014) - Gammage, Payam A; Rorbach, Joanna; Vincent, Anna I; Rebar, Edward J; Minczuk, Michal
Abstract We designed and engineered mitochondrially targeted obligate heterodimeric zinc finger nucleases (mtZFNs) for site‐specific elimination of pathogenic human mitochondrial DNA (mtDNA). We used mtZFNs to target and cleave mtDNA harbouring the m.8993T>G point mutation associated with neuropathy, ataxia, retinitis pigmentosa (NARP) and the "common deletion" (CD), a 4977‐bp repeat‐flanked deletion associated with adult‐onset chronic progressive external ophthalmoplegia and, less frequently, Kearns‐Sayre and Pearson's marrow pancreas syndromes. Expression of mtZFNs led to a reduction in mutant mtDNA haplotype load, and subsequent repopulation of wild‐type mtDNA restored mitochondrial respiratory function in a CD cybrid cell model. This study constitutes proof‐of‐principle that, through heteroplasmy manipulation, delivery of site‐specific nuclease activity to mitochondria can alleviate a severe biochemical phenotype in primary mitochondrial disease arising from deleted mtDNA species.